Influences on Behavioural Intentions for enrolment in Higher Education Institutions in India: A review of literature (International Journal of Food and Nutritional Sciences, 2022)
The media influence on consumer behaviour (student and parents) has been observed as more strong across print media than social media as education. Induced and cultured behavioural biases are indeed a big obstacle towards the successive adoption of marketing appeal. Especially with regard to course marketing and with regard to issue of admissions into higher education institutions, a plethora of research seeks to link ‘pre-existing’ cultured biases as restraining the admission initiative. The paper hence explores the literature and figures out the diverse theme bound influences that collectively shape up intentions for enrolment in Higher Education Institutions in India. The paper discusses the literature and explores the prominent Indian studies on subject matter.